ПЕДАГОГИК ТИЗИМЛАРНИ ЛОЙИҲАЛАШТИРИШ МАЗМУНИ, ТАРКИБИ ВА АСОСИЙ ЁНДАШУВЛАР - Ҳақназарова Нилуфар Қуранбоевна (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article explores the content, structure, and key approaches to designing pedagogical systems. It analyzes the interconnection and consistency between educational content, objectives, methods, and assessment systems. The impact of systematic, innovative, and active approaches on the effectiveness of the pedagogical process is also examined. The article provides a detailed discussion of the structural components of pedagogical systems, their interrelations, and the opportunities to improve the quality of education through the application of modern technologies.